2018
DOI: 10.20944/preprints201802.0027.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Design of Bubble Columns Equipped with a Fine Pore Sparger: Effect of Gas Properties

Abstract: Abstract:In our previous works we have proposed design equations that can predict with reasonable accuracy the transition point from homogeneous to heterogeneous regime as well as the gas holdup and the mean Sauter diameter at the homogeneous regime. The validity of the proposed correlations was checked with data obtained using different geometrical configurations and several Newtonian and non-Newtonian liquids as well as the addition of surfactants. However, in all the experiments the gas phase was atmospheri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…It is observed on Fig. 13 that the mean Sauter diameter, gas holdup and interfacial area are slightly affected by the type of gas employed, but significantly affected by the liquid phase, in agreement with Kanaris et al (2018) (Kanaris et al, 2018). The Sauter mean diameters of He in water and ethanol/water mixture are generally slight higher than those of N 2 under similar operating conditions (Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…It is observed on Fig. 13 that the mean Sauter diameter, gas holdup and interfacial area are slightly affected by the type of gas employed, but significantly affected by the liquid phase, in agreement with Kanaris et al (2018) (Kanaris et al, 2018). The Sauter mean diameters of He in water and ethanol/water mixture are generally slight higher than those of N 2 under similar operating conditions (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Table 1 summarizes available literature studies on the influence of operation parameters on bubble characteristics in bubble columns. Many research reported that with the increase of gas superficial velocity, the gas holdup enhanced, inducing an increase in bubbles number, turbulence and collision frequency, resulting in the increase of bubble size (Behkish et al, 2007;Clark, 1990;Kanaris et al, 2018;Lau et al, 2004;Luo et al, 1999;Majumder et al, 2006;Wilkinson et al, 1992). However, Mohagheghiana and Elbing (2018) and Akita and Yoshida (1974) both observed a decrease in Sauter mean diameter of bubbles with increasing gas superficial velocity.…”
Section: Wementioning
confidence: 99%
See 2 more Smart Citations
“…The BSD is shifted from smaller-sized bubbles to larger-sized bubbles, as shown in Figure . The reported increasing trend of d avg , with respect to u 0 , is consistent with literature data. However, as mathematically expressed in eq , increasing the u 0 substantially results in large We number flows, which, in turn, minimizes the probability of coalescence. This is attributed to the lower time for the film drainage to complete as bubbles collide.…”
Section: Computational Fluid Dynamics Model Developmentsupporting
confidence: 90%